Effects of hydration status during heat acclimation on plasma volume and performance - Pethick, W. A.; Murray, H. J.; McFadyen, P.; Brodie, R.; Gaul, C. A.; Stellingwerff, T. (Scandinavian Journal of Medicine & Science in Sports, 2019)
The impact of hydration status was investigated during a 5-day heat acclimation (HA) training protocol vs mild/cool control conditions on plasma volume (PV) and performance (20 km time-trial [TT]). Sub-elite athletes were allocated to one of two heat training groups (90 min/day): (a) dehydrated to ~2% body weight (BW) loss in heat (35°C; DEH; n = 14); (b) euhydrated heat (35°C; EUH; n = 10), where training was isothermally clamped to 38.5°C core temperature (Tc). A euhydrated mild control group (22°C; CON; n = 9) was later added, with training clamped to the same relative heart rate (~75% HRmax) as elicited during DEH and EUH; thus all groups experienced the same internal training stress (%HRmax). Five-day total thermal load was 30% greater (P < 0.001) in DEH and EUH vs CON. There were significant differences in the average percentage of maximal work rate (%Wmax) across all groups (DEH: 24 ± 6%; EUH: 34 ± 9%; CON: 48 ± 8%Wmax) during training required to elicit the same %HRmax (77 ± 4% HRmax). There were no significant differences pre-to post-HA between groups for PV (DEH: +1.7 ± 10.1%; EUH: +4.8 ± 10.2%; CON: +5.2 ± 4.0%), but there was a significant pooled group PV increase, as well as a 97% likely pooled improvement in TT performance (DEH: -1.8 ± 2.8%; EUH: -1.9 ± 2.1%, CON; -1.8 ± 2.8%; P = 0.136). Due to a lack of between-group differences for PV and TT, but pooled group increases in PV and 97% likely group increase in TT performance, over 5 days of intense training at the same average relative cardiac load suggests that overall training stress may also impact significant adaptations beyond heat and hydration stress.